The Influence of School Environment on Student Learning Motivation at MTs Darun Nahwi Singajaya Indramayu - Ahmad Fauzi (Manajia: Journal of Education and Management, 2025)
This study aims to determine the Influence of School Environment on Student Learning Motivation at MTs Darun Nahwi Singajaya. The population in this study were 3 teachers and all students totaling 79 people. Sampling used a technique to determine samples from a population that has certain characteristics only. The number of samples set was 38 students. Data collection techniques used were: observation, questionnaires and interviews. Questionnaire data were analyzed using a frequency table. While interview and observation data were analyzed using a quantitative descriptive approach which was analyzed through 3 stages, namely: Data reduction, Data presentation and Data verification. The results showed that the MTs Darun Nahwi school environment influenced student learning motivation. This can be proven from the percentage of influence of school environmental conditions, namely 60.53%, learning facilities 47.37%, learning infrastructure 50.03%, relationships between students 42.13%, relationships with teachers 68.42% and relationships with school staff 52.6%, school atmosphere 52.65%, the role of teachers as motivators in learning activities 73.53%, rules 54.91% and cooperation between teachers 63.16%. The obstacles faced by teachers in increasing student learning motivation are students' attitudes and interests in learning and limited learning facilities and infrastructure. Efforts to overcome obstacles include creating a pleasant learning atmosphere, giving prizes for achievements, implementing the rules as well as possible, optimizing the role of teachers as motivators, cooperation between teachers in improving the quality of learning facilities and infrastructure. The conclusion in this study is that the MTs Darun Nahwi school environment influences student learning motivation, both positive and negative.